The effect of ascorbic acid on the freezability of ram semen diluted with extenders containing different proportions of glycerol - Sönmez, M; Demirci, ER (Scientific Technical Research Council Turkey, 2004)
This study was conducted to investigate the effects of ascorbic acid on the freezability and spermatological characteristics of ram semen diluted with Tris-glucose-egg yolk based extenders containing different proportions of glycerol. Six Akkaraman rams were used. Semen was collected by electroejaculator once every 3 days. The spermatological characteristics of the collected semen samples were determined. Pooled and diluted semen was cooled slowly to +4 degreesC over 2 h. Cooled semen was divided into 20 groups. Each of the 20 semen groups was diluted at a 1:1 ratio with one of the extender groups containing different proportions of glycerol (0%, 1%, 3%, 5%, and 7%) and ascorbic acid (0, 0.5, 1 and 2 mg/ml). Diluted semen was packaged in 0.25 ml French straws and equilibrated for 4 h before freezing. The semen in straws was frozen in liquid nitrogen vapor. The semen was thawed for 25 s at +38 degreesC. There was no significant difference in the spermatological characteristics depending on the increase in the proportions of acorbic acid after glycerolization-equilibration and freezing-thawing. While the increase in glycerol level in diluted semen reduced motility (P < 0.05), it raised the dead spermatozoa rate, and damaged the acrosome rate and total abnormal spermatozoa rate (P < 0.05) after glycerolization and equilibration. However, the increase in the glycerol level in diluted semen raised motility, and damaged the acrosome rate and total abnormal spermatozoa rate (P < 0.05), while it reduced the dead spermatozoa rate (P < 0.05) after freezing and thawing compared to the control diluent. In conclusion, the best results after freezing and thawing were observed in diluted semen groups containing 5% glycerol although the increase in the glycerol level (3%-7%) after glycerolization and equilibration in diluted semen had negative effects on spermatological characteristics. Moreover, the increase in the proportions of ascorbic acid in extended semen did not change any spermatological characteristics.
Keywords: ram; semen; freezing; ascorbic acid; glycerol